TECTONIC EVOLUTION OF THE SOUTHWESTERN FRAMING OF THE SIBERIAN PLATFORM IN THE VENDIAN-CAMBRIAN ACCORDING TO PALEOMAGNETIC DATA - Kungurtsev L.V.; Berzin N.A.; Kazanskii A.Yu.; Metelkin D.V. (My University, 2001)
We report generalized paleomagnetic data on the Vendian-Cambrian island-arc complexes of the southwestern framing of the Siberian Platform. They allow restoration of the arrangement of fragments of paleoisland arcs in the modern tectonic collage of the Altai-Sayan folded area (ASFA) at two stages: Vendian-Cambrian and Middle-Late Cambrian. Analysis of these data allowed us to establish the major periods of tectonic evolution of the Siberian marginal structure from the time of formation of the island arcs to the stage of collision and attachment of terrains to the Siberian continent. Unlike the existing reconstructions of the structure and development of the ASFA, this reconstruction is based on new paleomagnetic data. It agrees with the available paleobiogeographic general conclusions and all geological data with minimum assumptions in interpreting the history of the geodynamic development of the region. The constructed model confirms the earlier conclusions about the leading role of strike-slip faults in the formation of the Central Asian structure.
Keywords: Cambrian; Vendian; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская::Вендский